Expanding the clinical and molecular spectrum of PRMT7 mutations: 3 additional patients and review. Issue 3 (5th February 2018) - Agolini, E.; Dentici, M.L.; Bellacchio, E.; Alesi, V.; Radio, F.C.; Torella, A.; Musacchia, F.; Tartaglia, M.; Dallapiccola, B.; Nigro, V.; Digilio, M.C.; Novelli, A.
Abstract : Protein arginine methyltransferase 7 (PRMT7) is a member of a family of enzymes that catalyze the transfer of methyl groups from S‐adenosyl‐l‐methionine to nitrogen atoms on arginine residues. Arginine methylation is involved in multiple biological processes, such as signal transduction, mRNA splicing, transcriptional control, DNA repair, and protein translocation. Currently, 7 patients have been described harboring compound heterozygous or homozygous variants in the PRMT7 gene, causing a novel intellectual disability syndrome, known as SBIDDS syndrome (Short Stature, Brachydactyly, Intellectual Developmental Disability, and Seizures). We report on 3 additional patients from 2 consanguineous families with severe/moderate intellectual disability, short stature, brachydactyly and dysmorphisms. Exome sequencing revealed 2 novel homozygous mutations in PRMT7 . Our findings expand the clinical and molecular spectrum of homozygous PRMT7 mutations, associated to the SBIDDS syndrome, showing a possible correlation between the type of mutation and the severity of the phenotype. Abstract :